(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: The use of Isoniazid Prevention Therapy (IPT) helps normalize the health issues of patients with TB. The majority of patients suffering from these diseases are from a low-income group with poor education. They do not have adequate knowledge related to prevention and approaches that reduce the occurrence of TB disease soon after ART initiation where risk is higher. Aim: The study aims to determine the incidence of tuberculosis disease among patients with HIV while taking IPT and after its completion. Materials and Methods: This is a retrospective, observational, longitudinal study that used existing records of patients from Department of Pulmonary Medicine, D Y Patil Medical College, Nerul, Navimumbai, Maharashtra, India. The period of the study was from January 2020 to June 2021. STATA statistical software Version 12 was used to analyse the data. The sample size was estimated based on simple proportion formula taking incident TB disease after starting IPT 1.5% based on the study in a similar setting. Results: In this study, 960 patients were involved with mean age of 30 years, ranged between 25-37 years. TB was developed in 9.2% patients, out of which, 2.2% of patients were diagnosed while receiving IPT and 6.97% after IPT. Moreover, 55.2% of patients were on this treatment at the last observation. The unfavourable count of patients was 152 (15.8%). Most of the patients with unfavourable follow-up outcomes were lost to follow-up. 0.6% of patients have stopped treatment during the follow-up and 28.9% was transferred out. Finally, 4.7% of patients died and remaining were recovered. Conclusion: Breakthrough TB was uncommon and shown a significant proportion of it occurrence in the first month of treatment. This could be due to difficulty in diagnosing TB disease with HIV. The proper screening of patients is essential for offering treatment and providing effective care services.